PERKEMBANGAN SUKSESI VEGETASI DI AREA REVEGETASI LAHAN PASCATAMBANG BATUBARA (STUDI KASUS DI PT AMANAH ANUGERAH ADI MULIA KABUPATEN TANAH LAUT) - Ana Wahdiana; Gusti Muhammad Hatta; Kissinger Kissinger; Mahmud Mahmud (Universitas Lambung Mangkurat, 2022)
The purpose of the study was to analyze the development of vegetation succession in the post-coal mining revegetation area of PT Amanah Anugerah Adi Mulia. The method used to collect data in the revegetation area is the Nested Sampling. The data collected in the form of individuals number, types of vegetation, and diameters of poles and trees. Data were analyzed by tabulating matrix and Indeks Nilai Penting (INP). There are 8 main types of revegetation plants, 16 types of natural growth and 40 types of undergrowth plants. There is a trend of increasing the number of plants that grow naturally at the level of seedlings, saplings, poles and trees in the revegetation area. Revegetation plants aged 7 years had the highest number of species. The dominant species at 1 year revegetation age for seedlings was sengon buto (Enterolobium cyclocarpum) with INP= 86,01%, sapling was E. cyclocarpum with INP= 106,15%. The dominant species at 3 years of revegetation age for seedlings was calliandra (Calliandra calothyrsus) with INP value = 75,57 %, sapling was sengon laut (Paraserianthes falcataria) with INP = 56,73%, pole level was P. falcataria species with INP = 162,85%. The dominant species at 5 years of revegetation age for seedlings was sisir liar (Cudrania cochinchinensis) with INP value = 108,38 %, sapling was C. cochinchinensis with INP = 103,59 %, pole level was mangium (Acacia mangium) with INP = 229,58 %, the tree level is mangium with INP = 211,74%. The dominant species at 7 years of revegetation age for seedlings was mahang (Macaranga gigantea) with INP value = 53,32%, sapling was M. gigantea with INP = 44,31 %, pole level was A. mangium with INP = 98,29 % , the tree level is P. falcataria with INP = 163,15%. Revegetation can facilitate the succession process in post-mining land.